2016
DOI: 10.1097/qad.0000000000001134
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of HIV rapid tests compared with fourth-generation enzyme immunoassays or HIV RNA tests

Abstract: In clinical settings, HIV rapid tests were less sensitive in high-income countries compared with low-income countries, missing about one in seven infections, possibly because of the larger proportion of acute infections in targeted populations. This suggests that in high-income countries, HIV rapid tests should be used in combination with fourth-generation EIA or NAAT tests, except in special circumstances. Prospective Registration of Systematic Reviews registration number CRD42015020154.Supplementary video li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…A systematic review of HIV rapid test performance compared with fourth-generation HIV testing found a pooled sensitivity of 94.5% slightly higher than what was observed in our study. [17] This reduced sensitivity is concerning and more needs to be done to ensure greater accuracy of rapid HIV testing in these settings. In addition to continued implementation of quality assurance measures, the use of nucleic acid amplification tests for those who test rapid HIV test negative should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of HIV rapid test performance compared with fourth-generation HIV testing found a pooled sensitivity of 94.5% slightly higher than what was observed in our study. [17] This reduced sensitivity is concerning and more needs to be done to ensure greater accuracy of rapid HIV testing in these settings. In addition to continued implementation of quality assurance measures, the use of nucleic acid amplification tests for those who test rapid HIV test negative should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The applicability of PCA analysis in segregating the spectral data set from recently infected plasma (spectra from intentionally contaminated plasma) and negative plasma was demonstrated as a potential HIV‐1 screening tool within the window period. The HIV‐1 p24 antigen within the plasma is normally detectable during the early stages of infection or before the seroconversion period . During pre‐seroconversion periods, HIV infection test targets HIV RNA and HIV provirus DNA, whereas some studies have targeted p24 antigen which is detectable in less than 14 days after initial exposure to the virus .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the error rate of the PPG, previous research has demonstrated that the PPG can accurately discriminate between men convicted of sex offenses against children from those who have not (e.g., Barbaree & Marshall, ; Freund & Blanchard, ; Lalumiere & Quinsey, ; McPhail et al, ). No test is without its limitations; however, widely accepted medical tests (e.g., hematologic blood values, endocrinologic hormone levels, blood pressure measurements, HIV screening tests) develop cut scores that balance specificity and sensitivity (e.g., Tan et al, ; Waaler, ). Given the potentially significant legal ramifications of showing a deviant PPG response profile, along with maintaining the delicate legal balance between public safety and protecting the individual rights of the examinee, it is better to have more false negatives than false positives.…”
Section: Discussionmentioning
confidence: 99%